Clinical and angiographic profile of congenital anomalous origin of coronary arteries - Rahman, F; Bannerjee, SK; Akhter, N; Anam, K; Rahman, M; Subedi, B; Haque, SS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):49-54 The abstract of this article is available on the PubMed website